2020
DOI: 10.1108/ijsms-02-2020-0020
|View full text |Cite
|
Sign up to set email alerts
|

Influence of gamification on perceived self-efficacy: gender and age moderator effect

Abstract: PurposeIn advanced societies, lifestyles are increasingly sedentary, and it is important to identify strategies to help people acquire healthy habits, such as exercise. The present study proposes the use of gamification as a strategy for encouraging users to exercise regularly, based on the possibilities offered by “smart” devices such as smartbands.Design/methodology/approachThe work analyzes how individuals experience their participation in a gamification program, on the premise that it should provide an exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 94 publications
3
15
2
Order By: Relevance
“…This inding corroborates claims that user characteristics afect their experiences with gamiied systems (e.g., [18,60]), as well as has been shown in the context of games (e.g., [61,76]). On the other hand, this inding is contrary to studies that found no moderator efect of gender [44,72,86]. A reason for that contradiction might be the gamiication design.…”
Section: Discussioncontrasting
confidence: 74%
See 3 more Smart Citations
“…This inding corroborates claims that user characteristics afect their experiences with gamiied systems (e.g., [18,60]), as well as has been shown in the context of games (e.g., [61,76]). On the other hand, this inding is contrary to studies that found no moderator efect of gender [44,72,86]. A reason for that contradiction might be the gamiication design.…”
Section: Discussioncontrasting
confidence: 74%
“…For instance, [67] found that gamiication only worked for boys; that is, a moderator efect of gender. In contrast, [72] found that gamiication inluences women and older people more. Similarly, results from [47] suggest gamiication only works for people with good attitudes towards it.…”
Section: Literature Reviewmentioning
confidence: 88%
See 2 more Smart Citations
“…It is also said that video games how developed more violent tendencies from the player due to negative habits and outcomes found within the game that tampers with the real-life behaviours of the young people that have tread a problem in the society of gaming [13,14]. Be that as it may, positivity can be given from video games as well that helps benefit and give motivations to the player in developing interests within the game's theme and world [15].…”
Section: The Behavioural Effects Of Games On Studentsmentioning
confidence: 99%